2011
DOI: 10.3109/09537104.2011.560306
|View full text |Cite
|
Sign up to set email alerts
|

Stroke prediction using mean platelet volume in patients with atrial fibrillation

Abstract: Platelet size, measured as mean platelet volume (MPV), is associated with platelet reactivity. MPV has been identified as an independent risk factor for future stroke and myocardial infarction. The aim of this study was to determine the association of MPV with the development of stoke in patients with atrial fibrillation (AF). MPV, N-terminal pro B-type natriuretic peptide (NT-proBNP), and high-sensitivity C-reactive protein (hsCRP) were analysed in 200 patients with AF (mean age 69 years; 56% male). The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…5 Moreover, Ha et al reported that MPV was a predictive marker for stroke; its predictive power for stroke was independent of age, gender, and other CHADS(2) score components in patients with AF. 6 They had to mention the presence or absence of atrial fibrillation or how many people were in atrial fibrillation.…”
mentioning
confidence: 99%
“…5 Moreover, Ha et al reported that MPV was a predictive marker for stroke; its predictive power for stroke was independent of age, gender, and other CHADS(2) score components in patients with AF. 6 They had to mention the presence or absence of atrial fibrillation or how many people were in atrial fibrillation.…”
mentioning
confidence: 99%
“…Increased MPV is associated with gestational diabetes mellitus [9], congestive cardiac failure [10], hypertension [11], hypercholesterolemia [12], smoking [13], stroke [14], and peripheral artery disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MPV is a risk factor for thrombosis. [20,21] Braekkan et al [22] stated that MPV is a risk factor for venous thromboembolism, and increasing MPV is associated with increased risk of total venous thromboembolism in their prospective, population-based study consisting of 25,923 participants. Acikgoz et al [23] reported that the presence of thrombosis is associated with higher MPV in Behçet's disease patients, and the increase in MPV is independent of the disease activity.…”
Section: Discussionmentioning
confidence: 99%